Mexico's Unrule of Law : Implementing Human Rights in Police and Judicial Reform under Democratization. - Uildriks, Niels (Rowman & Littlefield Pub. Group, 2010)
Mexico's crisis of security is unrelenting. Why is it so hard to establish the rule of law, and why does the country's justice system continue to struggle to deliver both security and adherence to democratic values and human rights? To answer these questions, Mexico Unrule of Law: Implementing Human Rights in Police and Judicial Reform under Democratization looks at recent Mexican criminal justice reforms, placing this Mexico City case study of the social and institutional realities of the evolvingpolice and justice system within the county's long-term transition from authoritarian to democrat.